Y-chromosome haplogroups and susceptibility to azoospermia factor c microdeletion in an Italian population. Issue 3 (8th December 2006) - Arredi, Barbara; Ferlin, Alberto; Speltra, Elena; Bedin, Chiara; Zuccarello, Daniela; Ganz, Francesco; Marchina, Eleonora; Stuppia, Liborio; Krausz, Csilla; Foresta, Carlo
Abstract : Background: A limited number of studies aimed at investigating the possible association of Y-chromosome haplogroups with microdeletions of the azoospermia factors (AZFs) or with particular infertile phenotypes, but definitive conclusions have not been attained. The main confounding elements in these association studies are the small sample sizes and the lack of homogeneity in the geographical origin of studied populations, affecting, respectively, the statistical power and the haplogroup distribution. Materials and methods: To assess whether some Y-chromosome haplogroups are predisposing to, or protecting against, azoospermia factor c (AZFc; b2/b4) deletions, 31 north Italian patients carrying the AZFc b2/b4 microdeletion were characterised for 8 Y-chromosome haplogroups, and compared with the haplogroup frequency shown by a north Italian population without the microdeletion (n = 93). Results and discussion: A significant difference was observed between the two populations, patients with microdeletions showing a higher frequency of the E haplogroup (29.3% vs 9.7%, p<0.01). The geographical homogeneity of the microdeleted samples and of the control population, controlled at microgeographical level, allows the possibility that the geographical structure of the Y genetic variability has affected our results to be excluded. Conclusion: Thus, it is concluded that in the north Italian population Y-chromosome background affects the occurrence of AZFc b2/b4 deletions.